Two faced visions: constitutional state and communitarian multiculturalism regarding the exercise of the right to religious freedom: Some cases - Sanjurjo Rivo, Vicente (Derecho Público Iberoamericano, 2015)
Globalization has contributed to a considerable increase in the movement of not only money and goods, but also of people. Those increasing migratory movements are produced to a world-wide scale and provoke an intensification of the cultural and religious heterogeneity of the destination countries. This creates new challenges to the Democratic Constitutional State, which must guarantee the exercise of religious freedom of people that practice different religions and affiliate to diverse religious confessions. On the other hand, this cultural and religious diversification encourages the aspiration to demand a legal treatment distinguished under the exercise of religious freedom, particularly and in regard to what this study, regarding to the display of religious symbols –fundamentally the hijab– in schools.